Friday

March 6, 2015

March 6, 2015

Posted by **Trista** on Saturday, April 7, 2007 at 3:59pm.

If f(x) = x^2 – 3x + 4

then substitute 0 for x to get f(0).

**Answer this Question**

**Related Questions**

physics - A speedboat increases its speed uniformly from v1 = 20 m/s to vf = 26 ...

chem - DrBob has given you the equation to use: k2 = [H^+][SO4^-]/[HSO4^-] and ...

Algebra - Please help to find x, y 1. 8x-y=17 6x+y=11 2. 5x-2y=17 2x+3y=3 ...

Algebra2????? - What would be the missing piece of information given the ...

Algebra 1 - 1.To solve the linear system below, which substitution of unkowns is...

math help & correction - Problem #1 Is this correct or wrong? Find the slope of ...

Algebra ?? - What would be the missing piece of information given the following ...

Math -algebra (check plz) - ok say i was trying to find y in this equation 2x + ...

math - what is the slope of-6,3 -2,-9 help -6,3 -2,-9 I take these are ...

math - Substitute -1 for x. Simplify. If f(x) = 4x-3, find the following. f(-1)